2016
DOI: 10.1097/j.pain.0000000000000521
|View full text |Cite
|
Sign up to set email alerts
|

Widespread somatosensory sensitivity in naturally occurring canine model of osteoarthritis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 51 publications
5
83
0
Order By: Relevance
“…Quantitative sensory testing (QST), a method of quantifying pain, has been used to demonstrate central sensitization in human OA 182,183 , experimental dog OA 184 and spontaneous dog OA 185 . QST has also been used to demonstrate the efficacy of dog total hip replacements for reversing hyperalgesia 186 , as occurs in humans 187 .…”
Section: A Means To Identify the Genetic Basis Of Analogous Diseasementioning
confidence: 99%
“…Quantitative sensory testing (QST), a method of quantifying pain, has been used to demonstrate central sensitization in human OA 182,183 , experimental dog OA 184 and spontaneous dog OA 185 . QST has also been used to demonstrate the efficacy of dog total hip replacements for reversing hyperalgesia 186 , as occurs in humans 187 .…”
Section: A Means To Identify the Genetic Basis Of Analogous Diseasementioning
confidence: 99%
“…Mechanical stimuli include touch, pressure, and vibration, and the information is transmitted through mechanoreceptors in the skin and travels along myelinated axons through the dorsal column‐medial lemniscal pathway. Commonly, von Frey filaments have been used in humans with SM15, 16 and in various studies of pain in dogs 23, 25, 26, 27, 28, 29, 32, 33. The use of von Frey mechanical testing has been found to be feasible and reliable31, 33 and in 1 study identified different thresholds in normal dogs compared to dogs with acute spinal cord injury 32.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal testing also has been used in humans15, 16, 17, 35 and dogs23, 24, 25, 26, 29 to evaluate neuropathic and chronic pain. Temperature and pain stimuli are carried by nonmyelinated C fibers through the spinothalamic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing veterinary patients can potentially bridge the gap between studies in preclinical laboratory animal models and human clinical trials, leading to proof of efficacy and benefits for the veterinary population, as well as providing a "pathway" for drugs and procedures to be further studied in humans. 53 In the veterinary clinical population there are many patients that provide excellent examples of a naturally occurring disease where intervention may be very similar to those in human patients, including osteoarthritis (OA) 54 and bone cancer. 55 A challenge in this regard is that even within a disease category such as OA, there may be significant differences between species in terms of disease onset (acute or chronic), progression (weeks versus months), onset of clinical symptoms versus when the disease began, etc.…”
Section: Veterinary Clinical Trials As a Bridge Between Preclinical Lmentioning
confidence: 99%